Impact of ground soybean and starch levels on the quality of meat from feedlot young Nellore bulls - Rossi, L. G. [UNESP]; Fiorentini, G. [UNESP]; Jose Neto, A. [UNESP]; Vieira, B. R. [UNESP]; Malheiros, E. B. [UNESP]; Borghi, T. H. [UNESP]; Berchielli, T. T. [UNESP] (Elsevier, 2016)
Twenty-eight young Nellore bulls (395 ± 32 kg initial body weight) were assigned to a completely randomized design (2 × 2 factorial design with 7 animals per treatment) to evaluate effects on the quality of meat. Diet treatments consisted of high (about 25%) or low (about 16%) starch levels, with or without ground soybean addition. Shear force was decreased in the meat from animals fed a low-starch diet (P = 0.0016). Meat from animals fed a high-starch diet had increased total concentrations of unsaturated (P = 0.0029) and monounsaturated fatty acids (P = 0.0253). Polyunsaturated fatty acid content increased in the meat from animals fed a diet containing soybean (P = 0.0121). High starch diets (> 25%) decreased the concentration of saturated fatty acids and increased the amount of unsaturated fatty acids in the meat from young Nellore bulls.
Keywords: Bos indicus; Corn silage; Fatty acid profile; Lipid; Meat quality